Monocyte-derived APCs are central to the response of PD1 checkpoint blockade and provide a therapeutic target for combination therapy. Issue 2 (19th July 2020) - Schetters, Sjoerd T T; Rodriguez, Ernesto; Kruijssen, Laura J W; Crommentuijn, Matheus H W; Boon, Louis; Van den Bossche, Jan; Den Haan, Joke M M; Van Kooyk, Yvette
Abstract : Background: PD1 immune checkpoint blockade (αPD1 ICB) has shown unparalleled success in treating many types of cancer. However, response to treatment does not always lead to tumor rejection. While αPD1 ICB relies on cytotoxic CD8 + T cells, antigen-presenting cells (APCs) at the tumor site are also needed for costimulation of tumor-infiltrating lymphocytes (TILs). It is still unclear how these APCs develop and function before and during αPD1 ICB or how they are associated with tumor rejection. Methods: Here, we used B16 mouse melanoma and MC38 colorectal carcinoma tumor models, which show differential responses to αPD1 ICB. The immune composition of ICB insensitive B16 and sensitive MC38 were extensively investigated using multi-parameter flow cytometry and unsupervised clustering and trajectory analyses. We additionally analyzed existing single cell RNA sequencing data of the myeloid compartment of patients with melanoma undergoing αPD1 ICB. Lastly, we investigated the effect of CD40 agonistic antibody on the tumor-infiltrating monocyte-derived cells during αPD1 ICB. Results: We show that monocyte-derived dendritic cells (moDCs) express high levels of costimulatory molecules and are correlated with effector TILs in the tumor microenvironment (TME) after αPD1 ICB only in responding mouse tumor models. Tumor-resident moDCs showed distinct differentiation from monocytes in both mouse and human tumors. We further confirmed significant enrichment of tumor-resident differentiated moDCs in patients with melanoma responding to αPD1 ICB therapy compared with non-responding patients. Moreover, moDCs could be targeted by agonistic anti-CD40 antibody, supporting moDC differentiation, effector T-cell expansion and anti-tumor immunity. Conclusion: The combined analysis of myeloid and lymphoid populations in the TME during successful and non-successful PD1 ICB led to the discovery of monocyte-to-DC differentiation linked to expanding T-cell populations. This differentiation was found in patients during ICB, which was significantly higher during successful ICB. The finding of tumor-infiltrating monocytes and differentiating moDCs as druggable target for rational combination therapy opens new avenues of anti-tumor therapy design.